Analisis Perbandingan Minat Berwirausaha Mahasiswa dari Perspektif Perbedaan Gender - Ahmadi Usman (JURNAL PENDIDIKAN DAN KEWIRAUSAHAAN, 2023)
Abstract: The extant literature showed that the result of study in comparison of entrepreneurial intention have inconclusive results in the context of gender difference in academic higher education institution. However, there has been little research which examines the study of comparison of entrepreneurial intention at the department of business in the context of vocational higher education institution. Therefore, this study aims to compare entrepreneurial intention of students in both the department of accounting andbusiness administration at Politeknik Negeri Ujung Pandang. Research method use in this research was a quantitative research and descriptive comparison. Total samples were students consisting of based on purposive sampling method. Data were obtained by spreading questionnaires via online. The research found that there was no significant difference between male students’ entrepreneurial intention compared to female students’ one in both the department of accounting and business administration in Politeknik Negeri Ujung Pandang. Further, independent sample t-test also indicated that there was no significant difference between entrepreneurial intention of students in the department of accounting compared to entrepreneurial intention of ones in the department of business administration in the perspective of gender difference.